Administration of Binahong (Cordifolia (Ten) Steenis Anredera) Leaves Extracts Reduced Body Weight and Visceral Abdominal Fat Mass in Obese Male Rats (Rattus norvegicus) With Moderate Physical Exercise - Valentine Retny Shiajanto; Alex Pangkahila; I Gusti Made Aman (IJAAM (Indonesian Journal of Anti-Aging Medicine), 2021)
Introduction: Overweight and obesity are abnormal conditions characterized by excessive fat accumulation in adipose tissue, to the extent that health is impaired. It is associated with a greater risk of various metabolic diseases. Binahong (Cordifolia (Ten) Steenis Anredera) leaves extract is known to contain flavonoids, saponins, and tannins that have an effect on weight loss and a decrease abdominal fat mass. This study aims to prove that the administration of binahong leaves extracts reduces body weight and visceral abdominal fat mass in obese male rats (rattus norvegicus) with moderate physical exercise. Methods: This research was a true experimental study with the post-test only control group design. The research subjects were 36 male rats divided equally into 2 groups, (18 rats each). The positive control group (P1) were treated with moderate physical exercise (20 min of swimming/day for 2 weeks) and oral aquadest (placebo) for 2 weeks, while the treatment group (P2) were treated with moderate physical exercise (20 min of swimming/day for 2 weeks) and oral binahong leaves extract of 400 mg/kg bW once a day for 2 weeks. Body weight and abdominal visceral fat mass were measured after 2 weeks of treatment. The daily remaining feed was observed to observe the food intake. Results: The results showed that the average body weight of P1 group was 288.6±6.11 g, whereas the P2 group was 272±6.48 g (p<0.001). The abdominal visceral fat mass in the P1 group was 9.24±0.48 g, while in the P2 group was 7.43±0.58 g (p<0.001). The median remaining feed in group P1 was 3 g, while in the P2 group was 9.54 g (p<0.001). Conclusion: Together, the results of this study suggested that binahong leaves extracts reduced body weight and visceral abdominal fat mass in obese male rats (rattus norvegicus) with moderate physical exercise.